Peran Tenaga Kerja dalam Peningkatan Produksi Bawang Merah di Kebun Praktek Fakultas Pertanian Universitas Nusa Nipa - Padeng, Elias Raymond; Noni, Sarlina (Department of Agribusiness, Halu Oleo University, 2021)
Labor can increase shallot's production because Labor is a tool to carry out the production process. The aim to analyze the role of Labor in increasing Shallot Production. Research adapted descriptive research, the data carried out by researchers from library research and field research. The data sources from respondents, and also from the research implementation 01 October-01 November 2021. Furthermore, the data collection methods used were observation and questionnaires by Descriptive Analysis Method and Spearman Rank Correlation Test Analysis. The results found that the role of Labor in increasing the productivity of shallot plants in the Unipa garden was classified as very important based on two indicators consisting of Labor and increased production, which had been researched on 30 respondents and the results of the correlation test that had been conducted, it can be seen a positive and significant value relationship between Role of Labor and the Increase of Red Onion Production in the Gardens of the Faculty of Agriculture, Nusa Nipa University.